Pengaruh penerapan carbohydrate loading modifikasi terhadap kesegaran jasmani atlet sepak bola - Utoro, Bayu Febri; Dieny, Fillah Fithra (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background: The reduction of glycogen stores gradually during sports activities affect the performance of athletes. Carbohydrate loading is a method that aims to increase the glycogen stores are expected to delay fatigue and prevent hypoglycemia at the time of the matchPurpose: The purpose of this study was to verify the effect of modification carbohydrate loading to the physical fitness and some indicators of nutritional status soccer athletesMethods: Experimental studies with approaches one group pre and post test design on 23 athletes aged 14-20 years in Diklat Sepak Bola Bintang Pelajar Semarang RegencyÂ  in July 2011. During one week the subjects were given a high carbohydrate intake approximately 70% of the total energy requirement (protein and fat are given to normal) and soccer practice programmed with moderate intensity in the first three days and continued the intensity of light at the second of three days. Measurements included weight, height, percent body fat, lean body mass, blood glucose levels and physical fitness with Asian Committee on the Standarization of Physical Fitness Test (ACSPFT) methodResults: There were significant differencesÂ  of physical fitness, physical fitness components (speed and cardiorespiratory endurance), body mass index, percent fat, lean body mass and blood glucose levels before and after treatment with p <0.05Conclusion: Modified carbohydrate loading effected on physical fitness of soccer athletes. Fat mass and lean body mass to be the most influence factors on physical fitness